2021
DOI: 10.7759/cureus.19758
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Pulmonary Tuberculosis, Abnormal Glucose Tolerance, and Type 2 Diabetes Mellitus: A Hospital-Based Cross-Sectional Study

Abstract: Introduction Tuberculosis (TB) is an infectious disease caused by Mycobacterium tuberculosis and is the second leading infectious cause of death worldwide. The higher prevalence of pulmonary TB in patients with type 2 diabetes mellitus (T2DM) is a well-known fact. The inverse relationship is also being increasingly recognized. Very few studies are available on the correlation of glycemic parameters with grades of sputum acid-fast bacilli (AFB) positivity and disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
1
1
1
Order By: Relevance
“…Previous research has reported that the prevalence of T2DM in the TB population reached approximately 33.3%. 40 Our study showed the prevalence of T2MD is reaching 20.28% in PTB patients, which is lower than the previous report. The possible reason for the results is that the subjects in this study are PTB patients rather than TB patients.…”
Section: Discussioncontrasting
confidence: 81%
“…Previous research has reported that the prevalence of T2DM in the TB population reached approximately 33.3%. 40 Our study showed the prevalence of T2MD is reaching 20.28% in PTB patients, which is lower than the previous report. The possible reason for the results is that the subjects in this study are PTB patients rather than TB patients.…”
Section: Discussioncontrasting
confidence: 81%
“…Более высокая концентрация в крови другого важного сахарида -глюкозы -может сопровождать течение туберкулезной инфекции [23], но такой важный показатель как уровень глюкозы связан со слишком большим количеством процессов в организме, поэтому опираться только на данный показатель невозможно [9,36].…”
Section: медиаторы липидной и углеводной природыunclassified
“…infectious death worldwide. It is a well-known fact that the prevalence of pulmonary tuberculosis is high in patients with type 2 diabetes mellitus (T2DM) [3].…”
Section: Introductionmentioning
confidence: 99%